Effect of polyaluminium chloride water treatment sludge on effluent quality of domestic wastewater treatment - Nansubuga, Irene; Banadda, Noble; Babu, Mohammed; Verstraete, Willy; Wiele, Tom Van de (African Journal of Environmental Science and Technology, 2013)
Water resources degeneration is accelerated by the discharge of untreated wastewater and its byproducts, hence, reuse of these wastes is a major contributor to sustaining fresh water for the coming decades. In this study, the reuse of polyaluminium water treatment sludge (PA-WTS) as a flocculant aid to improve the effluent quality of wastewater during primary sedimentation is evaluated and presented. PA-WTS was collected from Gabba water treatment plant (Gabba WTP) Uganda, after the coagulation-flocculation process that makes use of aluminium chlorohydrate (ACH). The average aluminium residue concentration in PA-WTS was 3.4 mg/L. During this study, batch laboratory experiments were conducted in a jar-test apparatus in which different doses of PA-WTS were added. The results obtained showed a decrease in total suspended solids (TSS), chemical oxygen demand (COD), total ammonium nitrogen (TAN), and total phosphates (TP) in the supernatant after 30 min of settlement. The optimal PA-WTS dosage of 37.5 mL/L significantly (P<0.05) increased the TSS, TP and COD removal efficiencies by 15, 22 and 30%, respectively. It can be concluded that the PA-WTS positively complimented the sedimentation process in the primary treatment of wastewater to achieve better effluent quality.
Keywords: Aluminium chlorohydrate, poly aluminium sludge, reuse, wastewater, water treatment sludge.